1996
DOI: 10.1056/nejm199612193352502
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the Duration of Mechanical Ventilation of Identifying Patients Capable of Breathing Spontaneously

Abstract: Daily screening of the respiratory function of adults receiving mechanical ventilation, followed by trials of spontaneous breathing in appropriate patients and notification of their physicians when the trials were successful, can reduce the duration of mechanical ventilation and the cost of intensive care and is associated with fewer complications than usual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
652
8
68

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,227 publications
(743 citation statements)
references
References 29 publications
15
652
8
68
Order By: Relevance
“…Decrease Variable Variable Variable Probable decrease [78][79][80] Daily assessment of readiness to wean Decrease Decrease Decrease Decrease Possible decrease [82] Daily interruption of sedation…”
Section: Variable No Impact No Impact No Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Decrease Variable Variable Variable Probable decrease [78][79][80] Daily assessment of readiness to wean Decrease Decrease Decrease Decrease Possible decrease [82] Daily interruption of sedation…”
Section: Variable No Impact No Impact No Impactmentioning
confidence: 99%
“…For example, Ely and colleagues showed that daily, structured evaluations of patients' readiness to wean decreased the median duration of mechanical ventilation by 1.5 days compared with usual care [82]. Likewise, daily interruption in continuous infusion sedatives (titrated to patient wakefulness) shortened the median duration of mechanical ventilation by 2.4 days and the median intensive care length of stay by 3.5 days [83].…”
Section: Ventilator Weaning and Extubation Protocolsmentioning
confidence: 99%
“…In these studies, the non-use of protocol has made the time of extubation become inaccurate, resulting in early extubation and unnecessary prolongation of the duration of the weaning process [5,6,13,[16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…2 Weaning accounts for 41% and 60% of the total ventilatory time in mixed, medicalsurgical ICU populations and in populations with chronic obstructive pulmonary disease (COPD), respectively. 3 Over the past decade, clinical investigations have focused on strategies to limit the duration of ventilation, for example, early identification of patients who are likely to be weaned, [4][5][6] tests of readiness to resume spontaneous breathing trials (SBTs), [7][8][9] and strategies to reduce support in patients who fail a SBT. [10][11][12] Several modes and techniques have been used to liberate critically ill adults from invasive mechanical ventilation.…”
Section: Résumémentioning
confidence: 99%
“…Compared with traditional care, protocols have been shown to decrease the time to ventilator discontinuation and the total duration of mechanical support. [4][5][6] However, many barriers exist to implementing weaning protocols in clinical practice. 13,14 Despite the wide use of mechanical ventilation and the recent proliferation of studies on mechanical ventilation discontinuation strategies, little is known about methods of discontinuing mechanical ventilation in clinical practice.…”
Section: Résumémentioning
confidence: 99%